Student Creativity in Learning of Physics Experiments - sujito (UHN IGB Sugriwa Denpasar, 2023)
Experimental physics courses are one of the courses of excellence. Students need to be trained on the process of designing school physics practices with creative thinking learning patterns on the courses they gained during their studies. the purpose of this article is emphasizing the aspects of creative thinking skills towards the preparation of future physics teachers. The problems that can be identified are: 1) the creativity of the physics teacher has not been able to convince students of the physical product; 2) the applied curriculum has not emphasized the development of aspects of creative thinking skills. The approach used to cultivate creativity is inquiry with a practical approach. The results of this research are able to differentiate reasons, analyze arguments, analyze possibilities and uncertainties, solve problems and make decisions. The students should be developed based on the need for practical models that can support the achievement of goals. The essence of physics is a process of thinking in constructing and applying abstract ideas and their logical interrelationship. Research reveals that creativity is mostly a decision about what or who should do. The creative thinking skills in experimental physics classes need to be possessed by potential physics teachers so that they can understand the basic concepts, and are skilled in finding other solutions. Creative thinking skills can't develop them well if they're not trained.